Analysis of Torodov’s Narrative Structure and Intrinsic Elements of the Play Bisma Gugur (The Fall of Bisma) by Ki Seno Nugroho - Ilyasa Azka Azif; Irfansyah Irfansyah (Gorga : Jurnal Seni Rupa, 2025)
Baratayuda War as the peak of the biggest war in wayang stories has various important plays, one of which is the fall of Resi Bisma by Worosrikandi marking the turning point of the Pandawa's victory. This study aims to describe the narrative structure contained in a shadow puppet show video entitled “Gugurnya Sang Resi Bismo, Di Tangan Worosrikandi” performed by Ki Seno Nugroho. The show video uploaded on the YouTube channel “Bagong Trend” at the 31:04 to 53:56 time span was studied using a descriptive qualitative approach, based on Tzvetan Torodov's narrative structure theory and structural method. The findings reveal that the narrative does not begin from the equilibrium phase but rather from an initial disequilibrium phase, marked by the horrific conditions of Tegal Kurusetra. Ultimately, the new equilibrium phase is achieved through Bisma’s death at the hands of Srikandi. This episode portrays the conflict between goodness and justice, embodied by characters such as Resi Bisma, Srikandi, and Prabu. Set against the backdrop of Tegal Kurusetra with its tense, tragic, and sorrowful atmosphere, Ki Seno Nugroho employs metaphorical, personification, and hyperbolic figures of speech to create a dramatic impression. The conclusion of this research indicates that the Torodov narrative structure can be applied to traditional wayang plays (lakon wayang), and the performance conveys a strong moral message about justice and the law of karma as its main values.